Penanganan Perdagangan Manusia Di Kamboja Dalam Perspektif Hukum Internasional - Fitri Sri Rahayu; Mas Putra Zenno Januarsyah (Jurnal Riset Multidisiplin Edukasi, 2025)
Human trafficking is a serious and growing crime, with Cambodia being one of the countries most vulnerable to this issue. This study aims to analyze the handling of human trafficking in Cambodia from an international law perspective. Using a qualitative method and literature review approach, the research draws on international conventions, reports from international organizations, and Cambodian national regulations. The findings indicate that although Cambodia has adopted several legal frameworks to combat human trafficking, implementation remains hindered by limited resources, corruption, and weak cross-border cooperation. Despite support from the international community, such as the Palermo Protocol, consistent law enforcement continues to pose a significant challenge. The study highlights the need for stronger law enforcement and improved victim rehabilitation systems to address the problem effectively. Greater collaboration between the Cambodian government, international organizations, and non-governmental organizations is essential. Such joint efforts are expected to create more effective solutions in combating human trafficking and enhancing protection for victims.